Development and performance of modified clay nanoporous pipe for subsurface irrigation - Abdullahi, Salisu (2021)
Clay pipes are continuously gaining prominence for irrigation water management in drier regions. However, information on soil wetting patterns is a key requirement for understanding subsurface irrigation system design and management, even though current approaches are mathematically complex. The aim of this study, therefore, is to develop porous clay pipes and evaluate their performance and use the pipes to evaluate the prospect of a newly proposed method of non-contact thermography for wetting pattern study under laboratory experimental conditions. To achieve this, clay soil from Rege pits and zeolite were used as raw materials for the production of pipes. American Society of Testing and Materials (ASTM) standard procedures were followed for soil physical properties, consistency and linear shrinkage tests. Chemical compositions of the samples, morphological characteristics of the samples and the produced pipes were analysed using Electron Dispersive Spectroscopy (EDS) and Scanning Electron Microscopy (SEM). The geometry, specific surface area, pore-volume, pore diameter, hydraulic characteristics and absorption capacities of the produced pipes were evaluated using standard methods. Three different pipe types: rubber, clay and modified clay (clay mixed zeolite) porous pipes were used for soil wetting pattern study in the laboratory using Plexiglas soil column packed with homogeneous sandy soil. FLIR E60 infrared camera was used for wetting pattern images acquisition at different application times. Supervised Classification method of Maximum Likelihood Algorithm in ArcGIS 10.7.1 software interface was used to analyse the images. From the results, the soil was found to be clay with 11 % sand, 34 % silt and 55 % clay, particle density and bulk density as 2.43 and 1.58 g/cm3 respectively. The addition of zeolite shows a decrease in both liquid limit, plastic limit and shrinkage of the clay from 50.7, 27.6 and 11.67 % to 43.7, 27.3 and 8.92 % respectively, with Plasticity Index (PI) from 11.67 to 8.92. The samples are aluminosilicate materials with silica and alumina as main constituents, and traces of iron, potassium and cobalt. The external and internal diameters of 12 clay pipes ranged from 3.7±0.05 cm and 2.1±0.05 cm, while 12 modified clay pipes are 3.7±0.12 and 2.3± 0.22 cm. The modified clay pipes recorded higher surface area, pore-volume, and pore diameters of 4.46±0.20, 0.001044±0.000054 and 6.29±0.42, respectively. Moreover, the modified pipes have a high absorption capacity to that of clay pipes. The pipes emission rates operated at 0.2 bar were 2.54, 2.26 and 2.84 L/h per meter length of rubber, clay and modified clay pipes, respectively. This study provides an insight into the suitability of known pottery clay soil for the production of clay porous pipes and zeolite significantly improve the hydraulic and performance properties of the produced pipes. For the proposed wetting pattern method, the result revealed that it can appropriately determine wetted dimensions from the analysed images, also the wetted areas recorded a higher range (14.00 - 46.73%) to clay pipes (17.83 - 41.00%). Therefore, conclude that the proposed methods can also provide an alternative for laboratory soil wetting pattern study of different soil types, as well as different soil profiling conditions.